2011
DOI: 10.1002/dneu.20953
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular matrix proteins and their receptors in the development of the vertebrate neuromuscular junction

Abstract: The vertebrate neuromuscular junction remains the best-studied model for understanding the mechanisms involved in synaptogenesis, due to its relatively large size, its simplicity of patterning and its unparalleled experimental accessibility. During neuromuscular development, each skeletal myofiber secretes and deposits around its extracellular surface an assemblage of extracellular matrix (ECM) proteins that ultimately form a basal lamina. This is also the case at the neuromuscular junction, where the motor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
112
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 255 publications
(371 reference statements)
1
112
1
1
Order By: Relevance
“…Therefore, further studies are required to determine whether the partial activation of MuSK by Lrp4 observed in heterologous cells is relevant to the apparent cooperation between Lrp4 and Dok-7 in MuSK activation in vivo. Because agrin is secreted into the synaptic basal lamina and binds not only Lrp4, but also a variety of other NMJ proteins including laminins and dystroglycans (31), agrin could have roles other than activation of MuSK through such interactions. However, it was reported that modestly increased expression of MuSK in the skeletal muscle induces NMJ formation in agrindeficient embryos, although highly increased expression induces postnatal lethality with abnormally scattered NMJ formation even in mice with intact agrin (29).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are required to determine whether the partial activation of MuSK by Lrp4 observed in heterologous cells is relevant to the apparent cooperation between Lrp4 and Dok-7 in MuSK activation in vivo. Because agrin is secreted into the synaptic basal lamina and binds not only Lrp4, but also a variety of other NMJ proteins including laminins and dystroglycans (31), agrin could have roles other than activation of MuSK through such interactions. However, it was reported that modestly increased expression of MuSK in the skeletal muscle induces NMJ formation in agrindeficient embryos, although highly increased expression induces postnatal lethality with abnormally scattered NMJ formation even in mice with intact agrin (29).…”
Section: Discussionmentioning
confidence: 99%
“…In epithelial cells, dystroglycan-mediated laminin assembly facilitates signals of polarity and STAT5 activation (Leonoudakis et al, 2010;Weir et al, 2006;Xu et al, 2009). In skeletal muscle cells, dystroglycan is necessary for sarcolemmal integrity ( Barresi and Campbell, 2006) and neuromuscular junction development (Singhal and Martin, 2011). In tissues of the central nervous system, dystroglycan functions as a plasma membrane targeting, anchoring and clustering protein in both neurons and glia, and participates in neuronal migration in the developing cortex and cerebellum (Waite et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent formation of the AZs depends on cues provided by the synaptic basal lamina, a layer of extracellular matrix (ECM) that occupies the synaptic cleft (Singhal and Martin, 2011). A key component of this is laminin-β2 (encoded by Lamb2), which combines with other subunits to form laminin-α2β2γ1, α4β2γ1 and α5β2γ1 (also known as laminin-221, -421 and -521, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…The laminin-β2 chain interacts with VGCCs on the presynaptic terminus, initiating AZ assembly (Chen et al, 2011;Nishimune et al, 2004). In addition to its functions in AZ assembly, the basal lamina is important for postsynaptic differentiation and maturation of the NMJ (Singhal and Martin, 2011).…”
Section: Introductionmentioning
confidence: 99%